Effects of low-level imidacloprid oral exposure on cholinesterase activity, oxidative stress responses, and primary DNA damage in the blood and brain of male Wistar rats. (1st April 2021) - Katić, Anja; Kašuba, Vilena; Kopjar, Nevenka; Lovaković, Blanka Tariba; Marjanović Čermak, Ana Marija; Mendaš, Gordana; Micek, Vedran; Milić, Mirta; Pavičić, Ivan; Pizent, Alica; Žunec, Suzana; Želježić, Davor
Abstract: Imidacloprid is a neonicotinoid insecticide that acts selectively as an agonist on insect nicotinic acetylcholine receptors. It is used for crop protection worldwide, as well as for non-agricultural uses. Imidacloprid systemic accumulation in food is an important source of imidacloprid exposure. Due to the undisputable need for investigations of imidacloprid toxicity in non-target species, we evaluated the effects of a 28-day oral exposure to low doses of imidacloprid (0.06 mg/kg b. w./day, 0.8 mg/kg b. w./day and 2.25 mg/kg b. w./day) on cholinesterase activity, oxidative stress responses and primary DNA damage in the blood and brain tissue of male Wistar rats. Exposure to imidacloprid did not cause significant changes in total cholinesterase, acetylcholinesterase and butyrylcholinesterase activities in plasma and brain tissue. Reactive oxygen species levels and lipid peroxidation increased significantly in the plasma of rats treated with the lowest dose of imidacloprid. Activities of glutathione-peroxidase in plasma and brain and superoxide dismutase in erythrocytes increased significantly at the highest applied dose. High performance liquid chromatography with UV diode array detector revealed the presence of imidacloprid in the plasma of all the treated animals and in the brain of the animals treated with the two higher doses. The alkaline comet assay results showed significant peripheral blood leukocyte damage at the lowest dose of imidacloprid and dose-dependent brain cell DNA damage. Oral 28-day exposure to low doses of imidacloprid in rats resulted in detectable levels of imidacloprid in plasma and brain tissue that directly induced DNA damage, particularly in brain tissue, with slight changes in plasma oxidative stress parameters. Graphical abstract: Image 1 Highlights: Male Wistar rats were orally exposed to low doses of imidacloprid for 28 days. Detectable levels of imidacloprid were found in plasma and brain tissue. Imidacloprid induced slight changes in oxidative stress parameters. Primary DNA damage was dose-dependent in brain cells.